Multidimensional Well-Being of Remote Workers: A Qualitative Comparison Between Full-Remote and Hybrid Workers - Ayu Safira, Nadia; Hanami, Yuliana; Batubara, Megawati (Analitika: Jurnal Magister Psikologi UMA, 2023)
The implementation of full-remote and hybrid working systems continues to improve and be maintained now. In addition to the convenience, remote working affects the psychological condition of workers. Human Resource (HR) workers who perform remote working need to ensure their psychological condition because they become role models for employees in the company. This study aims to get a comprehensive overview of the well-being of HR workers who implement full-remote and hybrid systems. Qualitative research methods are used with thematic comparison analysis. Data was collected through semi-structured interviews. The characteristics of the respondents in this study are 1) HR employees; 2) Work for a minimum of 6 months; 3) Implement a remote working system (full remote or hybrid working). The research respondents consisted of four people, which are two full-remote workers and two hybrid workers. This study shows that overall remote working can simplify the work processes of employees because its flexibility. On the other hand, the differences were found between the two types of remote working, specifically full-remote work system gives employees more flexibility in managing their work, but workers tend to feel social isolation. Meanwhile, the hybrid work system makes it easier for workers to meet social needs, but workers tend to increase physical complaints. The results of this study can become practical suggestions at the individual, managerial and organizational levels in providing specific guidelines for remote working.